(untitled) (Journal of Pathology of Nepal, 2016)
Pathologists spend most of their professional lives beyond direct view of the public, mostly inside the four walls of the lab. It is the clinicians who face the wrath of the public when something goes wrong. However, with the growing awareness of the public into the decisive role played by the Pathologists in the definitive diagnosis of the disease, the pathologists will soon be the target of the aggrieved patients and relatives.1 The issue of ethics can be dealt when professionalism comes before profession. "Professionalism in medicine requires that physician serve the interests of the patient above his or her own selfinterest." Professionalism aspires to philanthropy, answerability, excellence, duty, service and respect for others. "Professionalism in Pathology is based on the same tenets, but has additional dimensions."The qualities of professionalism for pathologists include 1. Communication with the patients and the clinicians. A small phone call with the clinician will solve most of the clinical mysteries not written in the lab requisition forms; 2. Empathy and Compassion towards patients’, colleagues’, and laboratory personnel’s culture, age, gender, and disabilities; 3. Demonstration of passion, respect and understanding towards the patients; 4. Adherence to guidelines and regulations of the regulatory and accrediting bodies; and 5.Profeciency and knowledge in one’s work is valued by the patients more than the credentials, which also enables one to identify deficiencies in peer performance. The basic competencies of professionalism are vital to every pathology report, which in turn is the mirror of the ethics practiced by the pathologist. Evaluating oneself is perhaps the most important tool in maintaining professionalism in the practice of pathology. One colleague recently defined professionalism as “all the things one does when no one is watching,” thus placing personal integrity at the top of the list.